Developing, delivering and documentingrehabilitation in a multi-centre randomised controlled surgical trial: experiences from the ProFHER trial. Issue 12 (December 2014) - Handoll, H. H. G.; Goodchild, L.; Brealey, S. D.; Hanchard, N. C. A.; Jefferson, L.; Keding, A.; Rangan, A.
Abstract : Objectives: A rigorous approach to developing, delivering and documenting rehabilitation within randomised controlled trials of surgical interventions is required to underpin the generation of reliable and usable evidence. This article describes the key processes used to ensure provision of good quality and comparable rehabilitation to all participants of a multi-centre randomised controlled trial comparing surgery with conservative treatment of proximal humeral fractures in adults. Methods: These processes included the development of a patient information leaflet on self-care during sling immobilisation, the development of a basic treatment physiotherapy protocol that received input and endorsement by specialist physiotherapists providing patient care, and establishing an expectation for the provision of home exercises. Specially designed forms were also developed to facilitate reliable reporting of the physiotherapy care that patients received. Results: All three initiatives were successfully implemented, alongside the measures to optimise the documentation of physiotherapy. Thus, all participating sites that recruited patients provided the sling immobilisation leaflet, all adhered to the physiotherapy protocol and all provided home exercises. There was exemplary completion of the physiotherapy forms that often reflected a complex patient care pathway. These data demonstrated equal and high access to and implementation of physiotherapy between groups, including the performance of home exercises. Conclusion: In order to increase the validity and relevance of the evidence from trials of surgical interventions and meet international reporting standards, careful attention to study design, conduct and reporting of the intrinsic rehabilitation components is required. The involvement of rehabilitation specialists is crucial to achieving this. Cite this article: Bone Joint Res 2014;3:335–40.